ANALISIS USAHA KERAMBA JARING APUNG, PROSPEK DAN KENDALA PENGEMBANGANNYA DI NAGARI TANJUNG SANI KABUPATEN AGAM PROVINSI SUMATERA BARAT - Hendrik, Hendrik (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
Sani Maninjau Nagari was conducted in May 2013 with a goal of research is to know the size of investments and the income derived from the business of tilapia KJA 10 and 20 bags by using some index investment criteria. The results showed for KJA businesses with 10 pockets for Rp.163.840.000 and investment required to invest Rp 20 bags. 322 140 000. profits each harvest for KJA 10 bags of Rp. 51,594,200 and for KJA 20 bags of Rp.107.589.300. invest-ment criteria based index values obtained BCR from 1.61 to 1.63, FRR 31.49 to 33.39, 2.29 PPC period - the period of 3.17, FCR from 1.29 to 1.31. The problem in the development KJA Maninjau is KJA number has exceeded the carrying capacity of the environment so necessary arrangements.